2016
DOI: 10.1088/1475-7516/2016/04/044
|View full text |Cite
|
Sign up to set email alerts
|

Extended scalar-tensor theories of gravity

Abstract: We study new consistent scalar-tensor theories of gravity recently introduced by Langlois and Noui with potentially interesting cosmological applications. We derive the conditions for the existence of a primary constraint that prevents the propagation of an additional dangerous mode associated with higher order equations of motion. We then classify the most general, consistent scalar-tensor theories that are at most quadratic in the second derivatives of the scalar field. In addition, we investigate the possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
514
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 397 publications
(527 citation statements)
references
References 33 publications
12
514
0
1
Order By: Relevance
“…Under the simplifying but reasonable hypothesis that the spin-2 sector does not hide any subtlety, Refs. [14,15,31,32] then showed that this is also the case for most of these generalized Horndeski models, but curiously enough, not all of them -confirming thereby that previously published arguments were incomplete. It was shown in [14,31,32] …”
Section: Generalized Horndeski Theoriesmentioning
confidence: 55%
See 4 more Smart Citations
“…Under the simplifying but reasonable hypothesis that the spin-2 sector does not hide any subtlety, Refs. [14,15,31,32] then showed that this is also the case for most of these generalized Horndeski models, but curiously enough, not all of them -confirming thereby that previously published arguments were incomplete. It was shown in [14,31,32] …”
Section: Generalized Horndeski Theoriesmentioning
confidence: 55%
“…(15) that we obtained in cosmology, which is not a surprise since the asymptotic behavior of the present solution at large radii should match with this cosmological solution. But we find here some restrictions with respect to (15): The f 3 function needs to be very precisely tuned at the cosmological value X = X c (in order not to contribute to any background equation at this precise value), while f 5 and s 5 should be related in a specific way at this value of X (again so that their sum Xf 5 + 2s 5 does not contribute to any background equation). It should be underlined that this set of equations (28) only needs to be satisfied at the cosmological value X = X c , and notably that (28c) and (28d) should not be imposed for all X.…”
Section: Schwarzschild-de Sitter Solutionsmentioning
confidence: 96%
See 3 more Smart Citations